Na+/K+-ATPase is present in scrapie-associated fibrils, modulates PrP misfolding in vitro and links PrP function and dysfunction. - James F Graham; Dominic Kurian; Sonya Agarwal; Lorna Toovey; Lawrence Hunt; Louise Kirby; Teresa J T Pinheiro; Steven J Banner; Andrew C Gill (PLoS ONE)
Transmissible spongiform encephalopathies are characterised by widespread deposition of fibrillar and/or plaque-like forms of the prion protein. These aggregated forms are produced by misfolding of the normal prion protein, PrP(C), to the disease-associated form, PrP(Sc), through mechanisms that remain elusive but which require either direct or indirect interaction between PrP(C) and PrP(Sc) isoforms. A wealth of evidence implicates other non-PrP molecules as active participants in the misfolding process, to catalyse and direct the conformational conversion of PrP(C) or to provide a scaffold ensuring correct alignment of PrP(C) and PrP(Sc) during conversion. Such molecules may be specific to different scrapie strains to facilitate differential prion protein misfolding. Since molecular cofactors may become integrated into the growing protein fibril during prion conversion, we have investigated the proteins contained in prion disease-specific deposits by shotgun proteomics of scrapie-associated fibrils (SAF) from mice infected with 3 different strains of mouse-passaged scrapie. Concomitant use of negative control preparations allowed us to identify and discount proteins that are enriched non-specifically by the SAF isolation protocol. We found several proteins that co-purified specifically with SAF from infected brains but none of these were reproducibly and demonstrably specific for particular scrapie strains. The α-chain of Na(+)/K(+)-ATPase was common to SAF from all 3 strains and we tested the ability of this protein to modulate in vitro misfolding of recombinant PrP. Na(+)/K(+)-ATPase enhanced the efficiency of disease-specific conversion of recombinant PrP suggesting that it may act as a molecular cofactor. Consistent with previous results, the same protein inhibited fibrillisation kinetics of recombinant PrP. Since functional interactions between PrP(C) and Na(+)/K(+)-ATPase have previously been reported in astrocytes, our data highlight this molecule as a key link between PrP function, dysfunction and misfolding.